Complete Laryngo-Tracheo-Oesophageal Cleft masquerading as Oesophageal Atresia and Tracheo-oesophageal Fistula: A Potential Diagnostic and Management Challenge - Goring, Jonathan (J Indian Assoc Pediatr Surg, 2020)
Newborn babies presenting with difficulties related to the aerodigestive tract (ADT) are often provisionally diagnosed and managed as having oesophageal atresia +/- tracheo-oesophageal fistula. Continuing difficulties with management and abnormal findings on investigations should lead to the consideration of other congenital anomalies of the ADT, including complete larnygo-tracheo-oesophageal cleft (LTOC). We present two patients who were eventually diagnosed with complete LTOC and care was withdrawn. We discuss the inherent difficulties in reaching this diagnosis and present an algorithm to help manage these rare and challenging situations.